Using the Word Association Test to Examine Life Skills Cognitive Structures of Pre-Service Science Teachers - Merve Bahar Alaca; Havva Yaman; Sibel Er Nas (Journal of Science Learning, 2020)
Science teachers, while teaching their students the science concepts, should also be teaching life skills. To ensure that future science teachers are competent to teach these skills, it can help assess the cognitive structures they hold as pre-service teachers. The current study aimed to reveal the cognitive structures and conceptual knowledge status of pre-service science teachers related to life skills. The participants were 165 pre-service teachers studying at the Department of Elementary Science Education at a public university in Turkey. A word association test (WAT) using six keywords (Communication, teamwork, entrepreneurship, creativity, decision making, analytical thinking) about life skills was developed. The gathered data was analyzed with the interslice distance technique and a descriptive analysis method. The results suggest that pre-service science teachers do not have the cognitive structures to produce enough answer words about life skills. It is suggested that elective undergraduate courses that allow students to recognize and internalize these skills can be introduced or increased in pre-service teaching programs.